Evaluation of the Radiopacity, pH, and Calcium Ion Release of Calcium Silicate and Epoxy Resin-based Endodontic Cements - Loyola-Cano, Milagros Judith; García-Rupaya, Carmen Rosa (Iranian Endodontic Journal, 2025)
Introduction: Endodontic cements are essential materials for achieving successful root canal treatment. Therefore, they must present adequate physicochemical properties to ensure optimal clinical performance. This study aimed to evaluate radiopacity, pH, and calcium ion release of calcium silicate- and epoxy resin-based cements/sealers. Materials and Methods: Four materials were evaluated: Vioseal, AH-Plus, AH-Plus Bioceramic Sealer, and MTA Angelus. Ten cylindrical specimens (10 mm diameter, 1 mm height) per group were prepared for each tested property, totaling 80 samples. The same specimens were used for pH and calcium ion release, while separate specimens were used for radiopacity. All samples were stored at 37°C and 95% humidity. Radiopacity was assessed by digital radiography using an aluminum step wedge (1-10 mm). pH was measured at 1, 7, and 14 days using a calibrated digital pH meter. Calcium ion release was determined using atomic absorption spectrophotometry. Data were analyzed using Kruskal-Wallis and Dwass-Steel-Critchlow-Fligner post hoc tests (P<0.05). Results: Vioseal and AH-Plus showed the highest radiopacity values (9.98±0.42 mm Al and 10.00±0.38 mm Al, respectively), while AH-Plus Bioceramic Sealer (9.04±0.28 mm Al) and MTA Angelus (4.72±0.40 mm Al) showed lower values. Regarding pH, AH-Plus Bioceramic presented the highest and most sustained alkaline value (up to 12.5), and AH-Plus the lowest (6.25±0.26). In calcium ion release, Vioseal showed the highest release on day 7 (29.4±3.12 ppm), while AH-Plus Bioceramic Sealer also peaked on day 7 (18.60±5.54 ppm); MTA Angelus presented its highest release on day 1 (11.80±1.00 ppm). Conclusion: All evaluated cements/sealers met the ISO 6876 standard for radiopacity. Calcium silicate-based cements showed an alkaline pH and sustained calcium ion release, whereas Vioseal presented an initially high and transient release.